Long-term follow-up of patients with MINOCA (myocardial infarction with unobstructed coronary arteries) undergoing intracoronary spasm provocation testing. (14th October 2021) - Pirozzolo, G; Seitz, A; Sechtem, U; Bekeredjian, R; Ong, P
Abstract: Background: Up to 30% of patients presenting with acute coronary syndrome undergoing coronary angiography are found to have no culprit lesion. Among them, epicardial or microvascular spasm can be diagnosed in ∼50% of patients undergoing provocative testing. While prognostic data in patients with coronary spasm and stable angina are abundant, the outcome of patients with myocardial infarction and unobstructed coronaries (MINOCA) and coronary spasm is not clear. Purpose: The aim of this study was to investigate the prognosis of a cohort of patients presenting with MINOCA undergoing intracoronary acetylcholine (ACH) spasm testing. Methods: We evaluated consecutive patients with MINOCA undergoing acetylcholine testing to detect epicardial or microvascular spasm from 2014 to 2017. Other aetiologies for MINOCA such as myocarditis, supraventricular tachycardia, pulmonary embolism etc. were excluded. Data regarding mortality (cardiac/non-cardiac), nonfatal myocardial infarction (MI), repeated coronary angiography and percutaneous coronary intervention (PCI) were recorded. Results: Of 112 patients in our study, follow-up data were available for 96 patients (86%, 51% women, mean age 63±13 years). Acetylcholine testing was positive in 51 (53%) patients. Among patients with a positive test, epicardial spasm was detected in 26 (51%) and microvascular spasm in 25 (49%) patients. After a median follow-up of 5±3.5 years, 7 deaths (7%) and 20 nonfatal myocardial infarctions (21%) occurred. Moreover, 19 patients (20%) underwent coronary angiography and 9 patients (9%) received a PCI. Comparisons of the Kaplan–Meier curves by log-rank test showed that patients with positive acetylcholine test had a worse outcome compared to those with a negative test in terms of death from any cause (p=0.01), myocardial infarction (p=0.03) and repeated coronary angiography (p=0.05). Conclusion: This follow-up study shows that prognosis of MINOCA patients with coronary spasm on provocative testing is worse compared to patients with an uneventful test. The results underline the potential prognostic value of spasm testing in MINOCA patients. FUNDunding Acknowledgement: Type of funding sources: None.